Mass cultivation and lipid production of microalgae nanochloropsis sp using 10l photobiorector for biodiesel production - Primilla, Paramasivam (2021)
The depletion of fossil fuel is closely associated with environmental degradation is predicted to become the biggest problem in the future. Burning fossil fuel generates air pollutants that can harm the ecosystem. Biodiesel has been one of the most promising alternative to substitute fossil fuel based diesel oil. The biodiesel content of edible feedstock is less renewable and lower in quantity. The transformation of these crops into large-scale production of biodiesel oil could lead to a global food supply deficit and global could face a food versus fuel dilemma immediately as a result. Fortunately, microalgae capable to grow in large scale and able to produce high lipid yield. In this study, attempts have been made to isolate and mass cultivate high lipid content microalgae from Teluk Cempedak, Kuantan coast, for biodiesel production. Among the collected samples, seven microalgae were screened and upon preliminary screening for morphological studies, green microalgae Nannochloropsis sp. was identified using fluorescence microscope and scanning electron microscope. Nannochloropsis sp. was found to be the most suitable microalgae with high growth rate and abundant of lipid content that has been cultivated under Conway medium. Stress factors influencing the intracellular lipid body were investigated. The effect of different light conditions, salinity and pH range were examined to determine the optimum factor for Nannochloropsis sp. growth and lipid enhancement. The combined optimized stress factors of annochloropsis sp. produced the highest lipid content of 64.8% which was cultivated in a 10-L photobioreactor. Lipid extraction was carried out using Bligh & Dyer, ultrasound and Soxhlet techniques. Among them, Soxhlet extraction method yielded the highest lipid content of 64.8% in 3 h extraction duration. The extracted lipid then transesterified with methanol to produce methyl esters (biodiesel) in 1.5 hours, where KOH was used as a homogenous catalyst. Thin layer chromatography (TLC) was done to ensure the conversion of Nannochloropsis sp. oil to biodiesel. GC-MS chromatogram depicts potential fatty acid methyl esters that include oleic acid (CI& 1) 72.6%, palmitic acid (C16o) 13.35%, linolenic acid (C1s3) 8.86%, stearic acid (Ciso) 3.07%, palmitoleic acid (CI61) 1.20%, eicosanoic acid (C2oo) 0.44% and gadoleic acid (C2o 1) 0.28%. The physical property of FAME was evaluated for refractive index (nO 20 °C) as 1.44 72, met the specification for biodiesel. Nannochloropsis sp. lipid have great potential to be used in biodiesel industry due to its composition of fatry acid methyl ester.